Adults' perceptions about whether children should disclose their mental illness. Issue 4 (19th December 2016) - Corrigan, Patrick; Buchholz, Blythe; Michaels, Patrick J.; McKenzie, Sue
Abstract : Purpose: Disclosure of mental illness is a key ingredient in contact-based public stigma change strategies. Adults who disclose their personal recovery story experience greater empowerment and heightened quality of life. Qualitative research suggests youth may similarly benefit, but also have unique benefits and costs associated with disclosure. The purpose of this paper is to examine adults' perceived costs and benefits of mental illness disclosure for middle and high school students with a new measure, the Coming Out with Mental Illness Scale for Children (COMIS-Child). Design/methodology/approach: In total, 300 adult participants from Amazon's MTurk completed the COMIS-Child, the Beliefs about Disclosure Scale (BDS), assessing perceptions about child disclosure, and the Attribution Questionnaire, assessing public stigma. Findings: Principal component analyses of the COMIS-Child yielded one factor representing disclosure costs and two factors for benefits (changing pubic stigma; person-defined benefits). Internal consistencies of the COMIS-Child factors were strong. Parents with children with mental illness endorsed more costs and fewer benefits from the changing public stigma factor than other respondents. Regression analyses showed decisions about youth disclosing mental illness from the BDS were associated with perceived costs, perceived benefits as personally defined, and public stigma. Disclosure beliefs were also inversely associated with public stigma. Social implications: Adults who identify more costs and fewer benefits were less likely to believe youth should disclose, favoring a more conservative approach to youth disclosure. This highlights the importance of participating in self-stigma interventions that guide an individual's decision making about disclosure. Originality/value: To the author's knowledge, this is the first study examining adults' perceptions of youth disclosure of mental illness.